Implementasi Undang-Undang No. 6 Tahun 2014 Tentang Desa Terhadap Pengangkatan Dan Pemberhentian Perangkat Desa Di Kecamatan Manggelewa Kabupaten Dompu - Rahmad Hidayat; M. Ulfatul Akbar Jafar; Eni Astuti H. M. Nur (JIAP (Jurnal Ilmu Administrasi Publik), 2019)
Based on Law No. 6 of 2014, village officials are appointed by the village head after consulting with the Camat on behalf of the Regent / Mayor. In this case the lifting and dismissal of the village apparatus must be in accordance with the Law and regulated by local regulations which refer to Law No. 6 of 2014 concerning villages in this case the Dompu Regency with Regional Regulation No. 2 of 2015 concerning procedures for appointment and dismissal of village officials. The aim is to determine the extent of the implementation of Law No. 6 concerning villages in upgrading and dismissing village officials and to find out what factors are inhibiting the appointment and dismissal of village officials in Manggelewa Sub-District, Dompu District. The research method used in this study is a qualitative method with data collection techniques used in this study: interviews, observation and documentation The results of this study indicate that the process of appointing village officials in Manggelewa Subdistrict is in accordance with the rules of both the law and regulations that refer to the law including permendagri No 67 of 2017 concerning the appointment and dismissal of village officials. Which is accommodated and implemented with the district regulation dompu No. 2 of 2015 concerning procedures for the appointment and dismissal of village officials. Which is where the Dompu district regulation takes the form of implementation and includes all terms and conditions. In terms of appointments, both general terms and administrative conditions where these conditions are the requirements points contained in Law No. 6 of 2014 concerning Villages. And the supporting factor is the existence of regency regulation dompu No. 2 of 2015 concerning procedures for the appointment and dismissal of village officials. While the inhibiting factor is the lack of resources, namely the ability of the village apparatus to implement the rules.